Rare case of medial Hoffa fracture with ipsilateral femur shaft fracture with unusual mechanism of injury - Katariya, Jeetendra; Khatri, Anup (International Journal of Research in Orthopaedics, 2024)
Hoffa’s fracture is a rare fracture which involves coronal fracture of the distal femur involving one or both the condyles. We report a rare combination of Hoffa fracture with ipsilateral femur shaft fracture with an unusual mechanism of injury. This case report will help increase awareness about such combined fracture pattern and eventually avoid missing these important intra-articular injuries- Hoffa’s fracture. In a patient with ipsilateral femur shaft fracture and in polytrauma patients, diagnosis of Hoffa’s fracture is very challenging because of presence of other long bone fracture and injuries. Missed Hoffa’s fracture in a patient with ipsilateral femur shaft fracture may restrict post-operative knee range of motion, knee pain, increased risk of early arthritis and joint deformity and stiffness.